PP06 Human factors – an experience driven approach!. (July 2018) - Harrison, Tracey; Robinson, Dave; Martin, Andy; Blood, Michaela; Clegg, Eleanor
Abstract : Aim: To explore the concepts of human factors through an interdisciplinary experience, highlighting the impact on individual's personal behaviours and of those around them. The overarching aim of the session is to link human factors and its relationship to patient safety. Delegates are encouraged to explore the concepts of human factors in an interdisciplinary setting. Objectives: This session introduces the delegates to the concept of Human Factors. Learners explore the implications of error, safety cultures and procedures whilst also looking at communication methods adopted in the clinical setting. Facilitated discussion allows delegates to identify the human factors, errors and potential pragmatic approaches to overcome safety issue after each scene of the case based video studies. Our aim after each session is a raised awareness of human factors to reduce the risk of incidents. Summary of work undertaken: We have developed a unique inter-disciplinary half day session with two video case studies. We worked alongside Dynamic business to produce two video recordings of serious untoward incidents (SUIs) that have occurred within the organisation. We recognised that through filming these incidents we were able to highlight when failures surrounding human factors occurred. We believe the case followed by facilitated discussion promotes reflective practice in our delegates allowing consideration for changes in future practice and sharing of experiences. Delegates are aware the cases are genuine which we think enhances the learning. We believe we are the only organisation to offer this unique method of delivery of Human Factors training within the region. We aim to develop the session and encourage specialities to run sessions for staff within that particular speciality. We also aim to develop the core faculty who facilitate the sessions, by involving a wide variety of 'human factors' enthusiasts from a range of staff groups and specialities will allow wider discussions within the groups. By examining two serious untoward incidents that occurred within the Trust demonstrates our commitment as an organisation to be a continually learning organisation, which promotes our mission statement to provide the highest quality healthcare at all times. Impact on practice: Though currently this course has only been run as a pilot course it received some very positive feedback from the delegates. We had a total of 11 delegates at our pilot session form a variety of specialities and job roles. We were fortunate to attract delegates' from ED, education, paediatrics as well as nursing and physicians associates. We attracted a variety of grades. We believe this multi-disciplinary approach to learning enables delegates to interact with colleagues in a safe learning environment. All of the delegates were able to identify at least two learning points they attained from the session. Out of the 11 delegates, 7 scored the session as 'excellent' with 4 scoring as very good (figure 1). In regards to the relevancy to their role and learning needs, 10 delegates scored this as strongly agree with 1 scoring as agree (figure 2).